Impact of a phone call with a medical student/general practitioner team on morbidity of chronic patients during the first French COVID-19 lockdown (COVIQuest): a cluster randomised trial. Issue 7 (28th July 2022) - Dibao-Dina, Clarisse; Léger, Julie; Ettori-Ajasse, Isabelle; Boivin, Estelle; Chambe, Juliette; Abou-Mrad-Fricquegnon, Karim; Sun, Sophie; Jego, Maeva; Motte, Baptiste; Chiron, Benoit; Sidorkiewicz, Stéphanie; Khau, Cam-Anh; et al.
Abstract : Objectives: The first COVID-19 lockdown led to a significantly reduced access to healthcare, which may have increased decompensations in frail patients with chronic diseases, especially older patients living with a chronic cardiovascular disease (CVD) or a mental health disorder (MHD). The objective of COVIQuest was to evaluate whether a general practitioner (GP)-initiated phone call to patients with CVD and MHD during the COVID-19 lockdown could reduce the number of hospitalisation(s) over a 1-month period. Design: This is a cluster randomised controlled trial. Clusters were GPs from eight French regions. Participants: Patients ≥70 years old with chronic CVD (COVIQuest_CV subtrial) or ≥18 years old with MHD (COVIQuest_MH subtrial). Interventions: A standardised GP-initiated phone call aiming to evaluate patients' need for urgent healthcare, with a control group benefiting from usual care (ie, the contact with the GP was by the patient's initiative). Main outcome measures: Hospital admission within 1 month after the phone call. Results: In the COVIQuest_CV subtrial, 131 GPs and 1834 patients were included in the intervention group and 136 GPs and 1510 patients were allocated to the control group. Overall, 65 (3.54%) patients were hospitalised in the intervention group vs 69 (4.57%) in the control group (OR 0.82, 95% CI 0.56 to 1.20; risk difference −0.77, 95% CI −2.28 to 0.74). In the COVIQuest_MH subtrial, 136 GPs and 832 patients were included in the intervention group and 131 GPs and 548 patients were allocated to the control group. Overall, 27 (3.25%) patients were hospitalised in the intervention group vs 12 (2.19%) in the control group (OR 1.52, 95% CI 0.82 to 2.81; risk difference 1.38, 95% CI 0.06 to 2.70). Conclusion: A GP-initiated phone call may have been associated with more hospitalisations within 1 month for patients with MHD, but results lack robustness and significance depending on the statistical approach used. Trial registration number: NCT04359875 .